MODEL BLENDED LEARNING SEBAGAI STRATEGI PEMBELAJARAN DI ERA DIGITAL - Bahraini Choliddiya Uddin; Noorma Dewi Firnanda; Yuliastutiek (CV. ADIBA AISHA AMIRA, 2024)
This study encourages discussion about how education should be positioned in the digital era and changing times. Researchers conducted a library survey to find several important parts in the teaching and learning process in the era of computers and the internet. In other words, the way students learn in the digital era is different from the way they learned in the past. This generation consists of individuals who have digital characteristics. Different from previous generations, students in this digital era were born and grew up with direct exposure to the digital world. Therefore, as learning partners, teachers must be able to create learning activities that enable students to obtain more information from the time they have. Combining face-to-face learning, face-to-face with technology, and information-based online learning is one way to achieve learning goals. In addition, the blended learning method has been proven to increase student satisfaction regarding learning and learning outcomes. This is because students have understood the flow of learning from the start and understand what is expected of them as well as the conditions for achieving goals and final assignments. Collaboration-based learning combines online and face-to-face learning. This means that implementation depends on technology. Schools wishing to implement this method must also have the equipment, infrastructure and financial support necessary for the technology. To utilize technology in learning activities, teachers must be able to evaluate and utilize data to improve student learning outcomes. With the blended teaching model, flexible learning really helps students because every lesson can be accessed anytime and anywhere. In addition, learning times and conditions can be adjusted to students' daily activities.